Doctor Who: Televized Science Fiction as Contemporary Melodrama. - Oglesbee, Frank W. (Extrapolation (Kent State University Press))
The article reviews the television series "Doctor Who," played by Tom Baker. It summarizes the concepts of science fiction and melodrama which were applied in the series. The nature of the series was being described and showed the theories that were applied to it in a practical manner. The show was distinguished with the other science fiction television programs. The success of the series has given rise to ancillary elements familiar in popular culture.